The Recent Crisis of the WTO Appellate Body: Is the WTO’s Reform a Solution? - Annisa, Intan Baretta Nur (Yustisia, 2022)
At the end of 2019, the international society was surprised by the cessation of the Dispute Settlement Body of the World Trade Organization (WTO) since the United States (US) blocked the election of the new judge of the Appellate Body (AB). This study examined the superiority and drawbacks of the implementation and capacity of the WTO dispute settlement body (DSB) to maintain the trading system among the state members. This paper finds that the WTO DSB plays a crucial role in the panel report’s acceptance. WTO also continues to develop and is characterized by a strict interpretation of the WTO treaties. Nevertheless, provisions were criticized, which made their implementation inefficient, such as retaliation, the lack of transparency, the restriction of amicus curiae briefs, the procedure of concession suspension, and the deficiency in the enforcement of the report by the injured party. The crisis that happened to the AB could trigger countries to revise the mistakes in the WTO whole system. This situation presents a chance to resolve issues about the output quality and institutional mandate observance of the WTO tribunals. Overall, the ideal option for member states is to continue incurring the costs of loss, develop a consensus, earn global benefits to keep the trading system running and support the WTO through active participation.